Teachers’ perspectives on the effectiveness of the rapid automatized naming program for students with dyslexia in Saudi Arabia - Alhossyan, Fawaz; Alnoaim, Jehad; Gharaibeh, Mahmoud; Etiwa, Mohamed Alhosany (Edelweiss Applied Science and Technology, 2025)
Dyslexia is a prevalent neurodevelopmental disorder that affects approximately one in five children, significantly impairing reading fluency, spelling, word recognition, and overall academic performance. Despite extensive research on the neurological basis of dyslexia, effective intervention strategies remain a critical challenge. This study examines teachers' perspectives on the effectiveness of the Rapid Automatized Naming (RAN) program as an intervention for students with dyslexia in Saudi Arabia. Utilizing a descriptive-analytical approach, the research explores the perceived impact of the RAN program on word recognition, reading fluency, and academic performance. A purposive sample of 150 teachers (75 male, 75 female) participated in the study. Data were collected through a structured questionnaire, validated by experts in special education, and tested for reliability using Cronbach’s alpha. Statistical analyses, including ANOVA and measures of central tendency, were conducted to assess the effectiveness of the RAN program, teaching strategies, and implementation challenges. The findings indicate that teachers perceive the RAN program as highly effective in improving reading skills and cognitive processing among students with dyslexia. However, moderate challenges in implementation were identified, including inadequate teacher training, limited resources, and difficulties in accommodating individual learning differences. The study underscores the necessity of targeted professional development to enhance teachers’ ability to implement the RAN program effectively. By addressing these challenges, the educational system can optimize intervention strategies for students with dyslexia. This research contributes to evidence-based practices in special education, advocating for inclusive and effective instructional approaches. Future studies should explore additional factors influencing the success of the RAN program and investigate strategies to enhance its implementation.